ANALISIS AIR CONDITIONER PADA KOMPLEK PERUMAHAN DI KOTA DENPASAR - Bhuana, I.G.A.T.; Kumara, I.N.S.; Giriantari, I.A.D.; Ariastina, W.G.; Setiawan, I.N.; Sukerayasa, I.W. (Jurnal SPEKTRUM, 2024)
Green building retrofit is an approach that involves modifying or enhancing existing buildings to achieve higher standards of sustainability and energy efficiency. By conducting an energy audit first, it's possible to identify potential energy savings in the housing, as well as components that need to be upgraded to reach the desired level of sustainability. Retrofit solutions may include the use of implementation of efficient HVAC systems, energy-saving lighting, and better energy management. The aim of this research is to explore the potential improvements that can be applied through Green Building Retrofit with a focus on energy efficiency and sustainability in Jadi Pesona II Barat Housing, comparing the energy consumption conditions of houses before and after the energy audit, as well as calculating the payback period for occupants after the retrofit implementation. After the energy audit and Green Building Retrofit, daily energy usage in homes in Perumahan Jadi Pesona II Barat decreased from 47.45 kWh per day to 36.91 kWh per day. This indicates a reduction of 10.54 kWh per day or approximately 22.22% from the previous conditions, and the payback period analysis results show that almost all air conditioners show values in line with the project investment feasibility parameter, which is below 4.2 years.